2019
DOI: 10.1186/s13567-019-0669-4
|View full text |Cite
|
Sign up to set email alerts
|

Amino acidic substitutions in the polymerase N-terminal region of a reassortant betanodavirus strain causing poor adaptation to temperature increase

Abstract: Nervous necrosis virus (NNV), Genus Betanodavirus , is the causative agent of viral encephalopathy and retinopathy (VER), a neuropathological disease that causes fish mortalities worldwide. The NNV genome is composed of two single-stranded RNA molecules, RNA1 and RNA2, encoding the RNA polymerase and the coat protein, respectively. Betanodaviruses are classified into four genotypes: red-spotted grouper nervous necrosis virus (RGNNV), striped jack nervous necrosis virus (SJNNV), barfin fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The temperature sensitivity of betanodaviruses seems to be regulated by RNA1 [35,151] and more specifically by the region encoding the amino acid residues 1-445 [151]. Experiments performed with a recombinant strain harboring six point mutations in this region confirmed its role in viral thermotolerance, and pointed to position 223 as a putative responsible for temperature regulation [36]. This study, however, showed that genomic regions other than 1-445 may be involved in NNV thermotolerance.…”
Section: Viral Thermotolerancementioning
confidence: 65%
“…The temperature sensitivity of betanodaviruses seems to be regulated by RNA1 [35,151] and more specifically by the region encoding the amino acid residues 1-445 [151]. Experiments performed with a recombinant strain harboring six point mutations in this region confirmed its role in viral thermotolerance, and pointed to position 223 as a putative responsible for temperature regulation [36]. This study, however, showed that genomic regions other than 1-445 may be involved in NNV thermotolerance.…”
Section: Viral Thermotolerancementioning
confidence: 65%
“…Nervous necrosis virus (NNV), one of the most devastating marine viruses, typically causes viral nervous necrosis (VNN) or viral encephalopathy and retinopathy (VER) in the larvae and juveniles of marine and freshwater fish (Souto et al, 2019). In recent years, NNV has spread to more than 50 fish species around Europe, Australia, Martinique, North America, Tahiti, and Asia (Liu et al, 2012;Doan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Definitive evidence such as a positive ELISA or IHC test or a protein misfolding cyclic amplification (PMCA) study of axis deer PrP C is needed to conclusively demonstrate axis deer are capable of contracting CWD. However, this research in combination with other work indicating a wider range of susceptible species than previously known [ 13 , 19 ], suggests axis deer in Texas and Hawaii may be susceptible to CWD, and should be managed as an at-risk species for CWD through the implementation of more formalized CWD surveillance. The proactive establishment of a CWD testing programme in axis deer wherever CWD has been detected in other species may be justified.…”
Section: Discussionmentioning
confidence: 72%
“…However, the highly conserved nature of PRNP within and among taxa may contribute to this finding [ 1 , 26 ]. Furthermore, a previous assessment of PRNP found PRNP to be monomorphic in roe deer ( Capreolus capreolus , n = 297) and fallow deer (n = 66) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation